Development of a quantitative method for sunitinib N-oxide - Yuya Ishikawa; Takuya Araki; Miki Takenaka Sato; Hideaki Yashima; Daisuke Nagano; Koujirou Yamamoto (Universitas Padjadjaran (Unpad), 2021)
We developed a simple method for quantifying sunitinib N-oxide (SNO) in human serum using a supported liquid extraction (SLE) method and liquid chromatography/tandem mass spectrometry (LC-MS/MS) to assess the impact of SNO on adverse drug reactions (ADRs) caused by sunitinib. SNO was extracted using an SLE method and analyzed using an Xevo-TQ (Waters) LC-MS/MS system. SNO and voriconazole (internal standard; ISTD) were detected in ESI positive mode, with transitions at 415.4/326.3 for SNO and 350.1/281.1 for voriconazole. The retention times of SNO and voriconazole were 2.25 and 2.67 min, respectively, and good calibration curve was obtained from 0.1–5.0 ng/mL for SNO. The regression equation (weight = 1/x2) describing the calibration curve in human serum was y = 2.81 × 10-9 x2 + 0.000253 x – 0.00202 (R2 = 0.990), where y is the peak area ratio of SNO against the ISTD and x is the nominal concentration of SNO. The intra- and inter-assay accuracy varied between -2.4 and 15.6% and all data except the limit of quantification (LOQ) were within ±10%. The precision varied between 6.7–15.4% and all data except LOQ were under 15%. The mean recovery ratio of SNO was 90.3 ± 4.9%, and the mean matrix factor was 0.96 ± 0.031. This is the first report of a method to quantify SNO in blood. This method will help in elucidating the effects of SNO in humans, contribute to the elucidation of the ADRs expression factors associated with sunitinib, and aid in optimizing treatment with sunitinib.